2004
DOI: 10.1063/1.1832758
|View full text |Cite
|
Sign up to set email alerts
|

Effects of periodic delta-doping on the properties of GaN:Si films grown on Si (111) substrates

Abstract: In this study, the effects of periodic Si delta-doping on the morphological and optical properties of GaN films grown on Si (111) substrate have been investigated. It is found that the flow rate of Si dopant during growth significantly affects the surface morphology, structural and optical quality of GaN. Compared to undoped GaN on Si(111), films grown using periodic delta-doping show a significant reduction of the in plane tensile stress, which is confirmed by the blueshift of the E2(TO) phonon and band edge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 25 publications
1
25
1
Order By: Relevance
“…5 Thus, precise phonon deformation potentials (PDPs), which relate Raman shift or split to stress, 6 are required. Although theoretical 7,8 and experimental works 7,[9][10][11][12][13][14][15] were reported, there is a considerable discrepancy among the reported figures. 9,10,16 This might be due to the conventional comparative experimental methodology, 14 which always faces the challenge of preparing GaN samples with a large range of biaxial stress.…”
Section: Introductioncontrasting
confidence: 40%
See 1 more Smart Citation
“…5 Thus, precise phonon deformation potentials (PDPs), which relate Raman shift or split to stress, 6 are required. Although theoretical 7,8 and experimental works 7,[9][10][11][12][13][14][15] were reported, there is a considerable discrepancy among the reported figures. 9,10,16 This might be due to the conventional comparative experimental methodology, 14 which always faces the challenge of preparing GaN samples with a large range of biaxial stress.…”
Section: Introductioncontrasting
confidence: 40%
“…11 For the A 1 (LO) phonon mode,K B was only experimentally calibrated a few times. The present value of 2.34cm -1 /GPa is closer to our previously reported value (2.76cm -1 /GPa).…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that the annihilation of threading dislocation during growth helps to relieve tensile stress of GaN film [7]. Pakula et.…”
Section: -10mentioning
confidence: 99%
“…The E 2 -high mode for sample A is 563.73 cm −1 while for sample B, it is shifted to 564.5 cm −1 . Compared with the standard value of 567.5 cm −1 for bulk GaN [5,7], the E 2 -high peaks for both samples show redshifts with respect to that of bulk GaN. Because of the lattice and the thermal mismatch, the GaN epilayer is subjected to a biaxial tensile stress when grown pseudomorphically on silicon (111) substrates.…”
Section: Methodsmentioning
confidence: 99%
“…Considerable efforts have been made to reduce the dislocation density and the residual strain to improve the crystalline quality of GaN samples deposited on silicon substrates. Silicon delta-doping, epitaxial lateral overgrowth, and substrate engineering have been proposed to improve the crystalline growth [4][5][6].…”
Section: Introductionmentioning
confidence: 99%